Injury surveillance in children--usefulness of a centralised database of accident and emergency attendances. - Lyons, R. A. (1995)
OBJECTIVE: To assess the usefulness of a centralised injury database in monitoring progress towards nationally set health targets for the reduction of childhood injuries. SETTING: West Glamorgan County, Wales. METHODS: Analysis was undertaken of data held in the West Glamorgan injury database which amalgamates population data with data from the three hospital units covering a population of 370,000. All first attendances due to a new injury in children aged 0-14 occurring in 1993 were analysed, with subgroup analysis for injuries occurring in the home and injuries resulting in fractures. Standardised injury ratios were compared with the distance travelled, car ownership, and Townsend index of deprivation at the ward level, using multiple linear regression. RESULTS: A total of 10,117 first time visits due to injuries were recorded, representing a rate of 182 injuries/1000 children aged 0-14 in West Glamorgan County. Distance from home to the accident and emergency departments was inversely correlated with total injury attendances, and injuries occurring at home, but not with injuries resulting in fractures. Visit rates for any type of injury were not associated with local car ownership rates or deprivation indices. CONCLUSIONS: Proximity to accident and emergency departments is a strong determinant of the use of the service by children with overall injuries, and injuries occurring at home. The lack of a significant association between travel distance and injuries resulting in fractures suggests that it is more meaningful to use a centralised database of accident and emergency department attendances to monitor the more severe spectrum of childhood injuries in assessing progress towards national targets for their reduction. The absence of an association between severe injuries and local socioeconomic factors suggests that national targets for the reduction of socioeconomic differentials in childhood injuries may need to be reassessed. These databases are also useful in generating information to direct preventive strategies and to target resources to areas of greatest need.